2017
DOI: 10.1002/mar.21029
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of social influence in piquing curiosity and influencing attitudes and behaviors in a social network environment

Abstract: Social networks provide an innovative means for facilitating social influence as well as arousing consumer curiosity. However, research on how social influence impacts attitudes and behaviors in this context is limited. Further, even less research exists examining how curiosity impacts consumers' behaviors, which is concerning since curiosity may be especially relevant in an online setting. To overcome these gaps, two studies were conducted which demonstrate that a consumer's curiosity toward a social network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 68 publications
1
26
0
2
Order By: Relevance
“…Despite the sizable literature on curiosity, little work has explored methods to influence curiosity by manipulating the social environment. Important exceptions include studies of the social nature of curiosity focusing on the role of group membership (Sinha, Bai, & Cassell, 2017a; Thomas & Vinuales, 2017), and models of how curiosity is influenced in social and group learning settings (Paranjape, Bai, & Cassell, 2018; Sinha, Bai, & Cassell, 2017b). For example, Sinha et al (2017a) used a data‐driven approach to identify behaviors that maximize an individual's probability of demonstrating curiosity during open‐ended problem‐solving in group work.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the sizable literature on curiosity, little work has explored methods to influence curiosity by manipulating the social environment. Important exceptions include studies of the social nature of curiosity focusing on the role of group membership (Sinha, Bai, & Cassell, 2017a; Thomas & Vinuales, 2017), and models of how curiosity is influenced in social and group learning settings (Paranjape, Bai, & Cassell, 2018; Sinha, Bai, & Cassell, 2017b). For example, Sinha et al (2017a) used a data‐driven approach to identify behaviors that maximize an individual's probability of demonstrating curiosity during open‐ended problem‐solving in group work.…”
Section: Introductionmentioning
confidence: 99%
“…Participants were informed that Jason shared these pictures in an album on Facebook where he has 225 Facebook friends. This design was used to encourage participants to project themselves into the scenario, a method commonly employed in the consumer behavior literature, specifically in the context of social media (e.g., Chari, Christodoulides, Presi, Wenhold, & Casaletto, 2016; Thomas & Vinuales, 2017). Participants were then randomly assigned to a likes condition.…”
Section: Studymentioning
confidence: 99%
“…So far, there have been only a few studies testing the idea that SSI predicts to what extent users are influenced by others in OSNs [11][12][13]. For instance, it has been found that SSI predicts who is affected by others' Facebook posts: susceptible Facebook users are affected by the content posted by all kinds of Facebook members, and unsusceptible Facebook users are affected only by "close" Facebook friends [11]. Likewise, SSI predicts the diffusion of word-ofmouth in OSNs.…”
Section: Competing Interestsmentioning
confidence: 99%
“…Finally, there is lack of resistance to social influence (LRSI), that is, one's lack of skepticism toward information from others and hence the tendency to undermine one's independence [8][9][10]. Having said this, a susceptible person compared with an unsusceptible person is typically more readily influenced by others-be it because of seeking information about a new product from others, because of conforming to others' expectations of what fashion style to wear, or because of not questioning others' posts about a political issue.So far, there have been only a few studies testing the idea that SSI predicts to what extent users are influenced by others in OSNs [11][12][13]. For instance, it has been found that SSI predicts who is affected by others' Facebook posts: susceptible Facebook users are affected by the content posted by all kinds of Facebook members, and unsusceptible Facebook users are affected only by "close" Facebook friends [11].…”
mentioning
confidence: 99%